Metacognitive Awareness Instruction: A Mixed Method Study on High School EFL Learners’ Writing Development - Akbarzadeh, Mahdieh (2020)
The goal of this study was to investigate the impact of using metacognitive awareness instruction (MAI) on EFL learners’ writing skill. To follow this goal, a research questions were designed and proposed. The questions sought to explore the impact of using metacognitive awareness instruction on the writing performance of the learners. To achieve this goal, two groups of high school EFL learners established the participants of the study. To collect the data of the study, three instruments were used: a test of homogenization, pre and post writing tests and finally intrinsic motivation questionnaire developed and examined by (Renee Payne, 2007). The achievements of the study indicated the positive impact of using MAI on the writing improvement of the learners.